Dietary Polyphenols Decrease Chemokine Release by Human Primary Astrocytes Responding to Pro-Inflammatory Cytokines - Mikolaj Grabarczyk; Dominika Ksiazek-Winiarek; Andrzej Glabinski; Piotr Szpakowski (MDPI AG, 2023)
Astrocytes are considered to be the dominant cell fraction of the central nervous system. They play a supportive and protective role towards neurons, and regulate inflammatory processes; they thus make suitable targets for drugs and supplements, such as polyphenolic compounds. However, due to their wide range, knowledge of their anti-inflammatory potential remains relatively incomplete. The aim of this study was therefore to determine whether myricetin and chrysin are able to decrease chemokine release in reactive astrocytes. To assess the antioxidant and anti-inflammatory potential of polyphenols, human primary astrocytes were cultured in the presence of a reactive and neurotoxic astrocyte-inducing cytokine mixture (TNF-α, IL-1a, C1q), either alone or in the presence of myricetin or chrysin. The examined polyphenols were able to modify the secretion of chemokines by human cortical astrocytes, especially CCL5 (chrysin), CCL1 (myricetin) and CCL2 (both), while cell viability was not affected. Surprisingly, the compounds did not demonstrate any antioxidant properties in the astrocyte cultures.